Clinical and intraoral findings of a patient with tricho-rhino-phalangeal syndrome type I - Karacay S; Saygun I; Tunca Y; Imirzalioglu N; Guvenc G (Wolters Kluwer Medknow Publications, 2007)
Tricho-rhino-phalangeal syndrome (TRPS) is a rare and an autosomal dominant disorder having the following characteristics: slowly growing sparse hair, medially thick, and laterally thin eyebrows, bulbous tip of the nose, long flat philtrum and thin upper lip with vermilion border, protruding ears, cone-shaped epiphyses and swelling. Our report intends to introduce TRPS to the dental literature and to present oral, clinical, and radiological data of a patient with TRPS. A rare association of supernumerary teeth was also diagnosed and one of them was extracted as it impeded on the eruption path of left premolar tooth.